2021
DOI: 10.1021/acs.jmedchem.1c00580
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin Structure and Permeability: From A to Z and Beyond

Abstract: Cyclosporins are natural or synthetic undecapeptides with a wide range of actual and potential pharmaceutical applications. Several members of the cyclosporin compound family have remarkably high passive membrane permeabilities that are not well-described by simple structural metrics. Here we review experimental studies of cyclosporin structure and permeability, including cyclosporin–metal complexes. We also discuss models for the conformation-dependent permeability of cyclosporins and similar compounds. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 161 publications
(310 reference statements)
0
59
0
Order By: Relevance
“…When permeating a membrane, the closed-form (1) or minor conformations in CHCl 3 , CHX, and HEX (twisted saddleshaped "baseball-stitch" conformation, C) were formed in the polar and apolar solvents, thus supporting the "congruent conformational states" model. 8 The conformational selectionlike (CSL) model 25 is considered to be an oversimplified model for CsA, as it was shown from our results that some common minor conformations in polar and apolar solvents might exist. When binding to the partner protein(s), it was speculated that a metal ion near the protein would interact with CsA to facilitate cis/trans isomerization and form 9−10 trans, thus generating the binding conformations (2−4).…”
Section: ■ Conclusionmentioning
confidence: 98%
See 1 more Smart Citation
“…When permeating a membrane, the closed-form (1) or minor conformations in CHCl 3 , CHX, and HEX (twisted saddleshaped "baseball-stitch" conformation, C) were formed in the polar and apolar solvents, thus supporting the "congruent conformational states" model. 8 The conformational selectionlike (CSL) model 25 is considered to be an oversimplified model for CsA, as it was shown from our results that some common minor conformations in polar and apolar solvents might exist. When binding to the partner protein(s), it was speculated that a metal ion near the protein would interact with CsA to facilitate cis/trans isomerization and form 9−10 trans, thus generating the binding conformations (2−4).…”
Section: ■ Conclusionmentioning
confidence: 98%
“…11,24 Very recently, an excellent review of cyclosporin's structure and its permeability was published. 25 These authors summarized chemical structures, dynamics, and permeability data for cyclosporin A and its analogues from the literature and proposed two permeation models: (i) the simplified inducedfit-like (IFL) model and (ii) the conformational-selection-like (CSL) model, which is a modified version of the congruent model proposed by Witek et al; 8 membrane permeation is assisted by congruent conformations, which are significantly populated in water and the membrane.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Their size allows these molecules to effectively disrupt protein–protein and protein–nucleic acid interactions, and their cyclic nature and larger size can confer high affinity and specificity for their targets. However, larger compounds cannot usually cross biological membranes, which prevents them from reaching intracellular targets and inhibits their absorption through the gastrointestinal tract, reducing oral bioavailability. Cyclic peptides and nonpeptide macrocycles typically lie outside standard definitions (SD) of drug-likeness, such as Lipinski’s rule of five (Ro5), and are frequently known as “beyond rule of five” (bRo5) molecules. There are some examples of bRo5 compounds that are membrane-permeable, such as the 11 amino acid residue macrocyclic peptide cyclosporin A, which has good oral bioavailability and is clinically used in oral drug formulations. , A recent review by Nielsen et al . identified 125 cyclic peptides that are orally absorbed in mammals.…”
Section: Introductionmentioning
confidence: 99%
“…There are some examples of bRo5 compounds that are membrane-permeable, such as the 11 amino acid residue macrocyclic peptide cyclosporin A, which has good oral bioavailability and is clinically used in oral drug formulations. 5,6 A recent review by Nielsen et al 7 identified 125 cyclic peptides that are orally absorbed in mammals. These examples raise important questions regarding the factors that enable some macrocyclic compounds to cross cell membranes and whether we can create models to predict membranepermeable bRo5 compounds.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 For example, cyclosporine A relies on a switch between conformations to enter cell membranes. 7 Increasing backbone flexibility has led to the reduction of the koff for stapled peptide macrocycles binding to receptor protein 14-3-3. 8 Conformational selection and multi-step, dynamic association processes are common in protein-protein interactions, 9 and strategies for controlling the conformational state of potential inhibitors are in demand.…”
mentioning
confidence: 99%